Malnutrition Among Pre-Dialysis Patients of Chronic Kidney Disease - Aqeel Ahmed, Muhammad Mohsin Riaz, Mohammad Faizan Riaz, Sadaf Zahid, Tooba Ahmad, Aleezay Tariq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of malnutrition among pre-dialysis patients of chronic kidney disease presenting to a tertiary care hospital. Methodology: This cross sectional study was conducted at Nephrology department, Jinnah hospital, Lahore during the year 2019, we enrolled a total of 200 pre dialysis patients of both gender presenting with chronic kidney disease. In All patients underwent measurement of weight in kilogram using digital weighing machine while height was measured by measuring scale with precision of 1mm using standard protocol. BMI was calculated, and all findings were recorded. Results: Age range in this study was from 20 to 80 years with mean age of 47.605±8.34 years. Male gender was dominant in this study with 73% patients as compare to 27% females. Malnutrition among pre-dialysis patients was seen in 46% patients. Conclusion: Pre-dialysis CKD patients frequently experience malnutrition. Malnutrition rates rise with both age and declining renal function. These patients require frequent and early evaluations of their nutritional status. Keywords: Chronic kidney disease, Pre-dialysis, Malnutrition